Efektivitas Kegiatan Shelving terhadap Temu Kembali Informasi Pemustaka di Dinas Kearsipan dan Perpustakaan Provinsi Sumatera Barat - Muhazra, Muhazra; Marlini, Marlini (Al-DYAS, 2024)
This research aims to evaluate the effectiveness of shelving activities on user information retrieval at the Archives and Library Service of West Sumatra Province. Using descriptive methods, this research involved 99 respondents who were randomly selected using random sampling techniques. Data was collected through a questionnaire consisting of 32 statements. The research results show that the effectiveness of shelving has a positive and significant effect on user information retrieval. The shelving variable obtained a percentage value of 71.78% (good category), while the information retrieval variable reached 76.18% (good category). The effectiveness of shelving has a significant effect on information retrieval by 52.5%. Although the overall assessment was positive, the research identified several areas requiring improvement, particularly in the aspects of accuracy of collection organization and shelving activities. Improvements in these aspects are expected to further increase user satisfaction and the effectiveness of information retrieval in the library.